Skrining kesehatan mental terhadap mahasiswa baru Fakultas Kedokteran - Karim, Fatmawati; Suciati, Tri; Amalia, Ella; Ikhsan, Diyaz Syauki; Aini, Syarifah (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2023)
Good mental health is needed to support the smooth learning process. Students have different learning patterns from high schools, so they must be able to adapt to the learning process. New student’s mental health screening is needed to be detected earlier. Medical Faculty (FK) Unsri has undergraduate programs (PS) such as Medical Education (PSPD), Dentistry (PSKG), Nursing (PSIK) and Psychology (PS Psychology). The educational process in FK, which is different from other faculties, can affect students' mental health. Academic and non academic problems encountered during the educational process, hinder students in their education. The aims was to determine mental health such as mental emotional disorders, the saturation and learning motivation of new undergraduate students at FK Unsri. There were 444 of 513 new students (86.54%) who were involved in this mental health screening, which PSKG (96%), PSPD (94.74%), PSIK (86.07%) and PS Psychology (47.83 %). Screening the saturation level using the Boredom Proness Scale (BPS) found that 7 (1.58%) new students were in category 4 who needed more attention from academic supervisors. Screening for mental-emotional disorders is carried out using the Self-Reporting Questionnaire (SRQ), in which 34.23% of new students have mental-emotional disorders. While the SMMS was only conducted for PSPD and PSKG students, it was found that 83.01% of students had good motivation, while 16.99% had less motivation. The results of this screening are quantitative in nature, which can be used as input and initial data for academic supervisors so that the student education process can run well.